Preferensi Terhadap Marketplace Menggunakan Metode Simple Additive Weighting (SAW) (Studi Kasus: Shopee dan Tokopedia) - Ellen Arnetta; Magdalena A. Ineke Pakereng (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
At this time technology has been growing, one of which is the development in the business world from tradional to digital. E-commerce as the main of contributor in Indonesia digital economy. Tokopedia and Shopee are two giants that dominate the Indonesia market. The researcher are interested in conducting research to determine customer interest and making choices to shop online. The method used in this research is SAW (Simple Additive Weighting) method and distributes questionnaires to marketplace users. The results obtained from Shopee's research have a preference value of 0.98 and Tokopedia's 0.91. These results show that the majority prefer to shop online using Shopee instead of Tokopedia.